Olfactory receptors in macrophages and inflammation - Orecchioni, Marco; Matsunami, Hiroaki; Ley, Klaus (Frontiers in Immunology, 2022)
Olfactory receptors (OR) that bind odorous ligands are the largest family of G-protein coupled receptors. In the olfactory epithelium, about 400 and 1,100 members are expressed in humans and mice, respectively. Growing evidence suggests extranasal functions of ORs. Here, we review OR expression and function in macrophages, specialized innate immune cells involved in the detection, phagocytosis and destruction of cellular debris and pathogens as well as initiation of inflammatory responses. RNA sequencing data in mice suggest that up to 580 ORs may be expressed in macrophages. Macrophage OR expression is increased after treatment with the TLR4 ligand lypopolysaccaride, which also induces transcription of inflammasome components. Triggering human OR6A2 or its mouse orthologue Olfr2 with their cognate ligand octanal induces inflammasome assembly and secretion of IL-1β, which exacerbates atherosclerosis. Octanal is positively correlated with blood lipids like low density lipoprotein (LDL)-cholesterol in humans. Another OR, Olfr78, is activated by lactate, which promotes the generation of tumor-associated macrophages that dampen the immune response and promote tumor progression. Olfactory receptors in macrophages are a rich source of untapped opportunity for modulating inflammation. It is not known which of the many ORs expressed in macrophages promote or modulate inflammation. Progress in this area also requires deorphanizing more ORs and determining the sources of their ligands.